PELAKSANAAN TUGAS HOUSEMAN DI PUBLIC AREA HOTEL GRAND BUNDA BUKITTINGGI - Perdana, Chaesar Sauqy; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Purpose of this final project is to find out the implemenmtation of houseman duties in the public area of Grand Bunda Hotel. Houseman is one of the parts that plays an important role in the Grand Bunda Bukittinggi Hotel. A houseman does their job in accordance with the SOP (Standar Operational Procedure), is responsible for providing a good and comfortable welcome to guests in finding a room. This research use qualitative research methods. Based on research conducted by the author, the obstacles that exist in the hotels are lack of housekeeping employees, and the lack of a toilet floor dryer. It is recommended that the hotel should add more employees so as not be overwhelmed when other employees are on leave. Keywords: Houseman, Hotel